Estrogen replacement therapy: effects of starting age on final height of girls with chronic kidney disease and short stature - Davoud Amirkashani; Farzaneh Rohani; Mahmoud Khodadost; Rozita Hoseini; Hamidreza Alidoost; Sedigheh Madani (BMC, 2022)
Abstract Introduction We investigated the age of starting Estrogen replacement therapy as a key parameter for reaching near normal Final Height (FH) in Chronic Kidney Disease (CKD) girls with growth retardation. Method This open label, quasi-experimental designed and matched controlled clinical trial was performed on CKD girls with short stature and later onset of puberty or delayed puberty according to clinical and laboratory investigations. Participants of group 1 and 2 had been treated with Growth Hormone (GH), and Ethinyl Estradiol (EE). EE was administered from 11 and 13 yrs. old in groups 1 and 2 respectively. Group 3 was selected from patients that did not accept to start GH or EE till 15 years old. The effect of the age of starting EE on FH, GH therapy outcomes, bone density, and calcium profile were evaluated. Result Overall, 16, 22, and 21 patients were analyzed in groups 1, 2, and 3 respectively. Mean Mid-Parental Height (MPH) had no significant difference between the 3 groups. GH therapy significantly enhanced mean FH in groups 1 and 2 in comparison with group 3 (β = − 4.29, p < 0.001). Also, multivariable backward linear regression illustrated significant negative association between FH and age of starting EE (β = 0.26, p < 0.001). Mean Para Thyroid Hormone (PTH), mean femoral and lumbar bone density were significantly enhanced after GH and EE therapy (p value: < 0.001). Conclusion We recommend starting EE from 11 yrs. old in CKD short stature girls who have no clinical and laboratory sign of sexual maturity at 11 yrs. to enhance the cost effectiveness of GH therapy.